Analisis Deiksis Dalam Film “Mencuri Raden Saleh” Karya Angga Dwimas Sasongko - Ananda Fatimah Azzahro; Nyar Osmi Arianti; Aditya Rahayu; Afina Maharani; Elisa Natika Hutabarat; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Student Research Journal, 2024)
Deixis are various things that relate closely to the grammaticalization of the characteristics of a language context or linguistic events relevant to linguistic interpretation, which is highly dependent on the context itself. Dialogues in movies can bring up various deixis, such as in "Stealing Raden Saleh" by Angga Dwimas Sasongko. This research aims to describe the relationship of literary works in the form of films with the use of deixis in it and also explain the types of deixis that consist of personal deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis. The method used by the researchers for analyzing data is descriptive qualitative with attention to pragmatic studies. The results of data analysis are in the form of dialogs contained in the film that match the types of deixis. Analysis was done with several stages, such as recording, analyzing, identifying, and classifying dialogues based on the types of deixis. Five types of deixis were found, namely personal deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis. The analysis in this research can provide more insight and knowledge about deixis, especially its type and implementation based on speech.